The alchemy of the dhikr ritual: South African Sufi women experiences - Mitha, Kareema (Department of Religious Studies, 2025)
This research examines the embodied ritual practices and processes of self-cultivation experienced by South African Sufi women, contextualising these within the historical, cultural, and gendered frameworks that have long shaped religious and social life in South Africa. Situated in feminist theory, the study adresses the historical marginalisation of women's voices in both Islamic and South African socio-religious discourses, focusing on how patriarchal structures and apartheid-era segregation influenced the development of religious practices of Muslim communities. In these communities, Sufi women engage in transformative practices like dhikr (remembrance of God), positioning ritual as both a means of spiritual deepening and a method of self-realisation that helps them navigate and reshape personal and collective identities. Anchored in the Sufi metaphor of life as a ‘journey,' this research illustrates how these embodied spiritual practices support women's self-formation, empowering them to negotiate layered identities and respond to sociopolitical forces with resilience and intentionality. The study's interdisciplinary approach draws on religious studies, Islamic psychology, theological anthropology, and gender theory to explore how these women's spiritual journeys serve as acts of self-articulation, connection, and resistance. Through an analysis of themes like identity, community, and the guidance provided by their Shaykh, the research captures the dynamics of self-identity, belonging, and personal agency. The participants' evolving identities are analysed within their socio-religious environments, revealing how spiritual practices help them cultivate awareness and self-understanding within a framework of resilience and openness. By highlighting their progression toward oneness— grounded in both a sense of individuality and a unified spiritual purpose—the study also reveals the ethical and communal values these women cultivate. Through community bonds and spiritual mentorship, they integrate values of self-awareness, empathy, and shared growth, reinforcing a collective ethical compass in line with their spiritual goals.